Intrathoracic Caecal Perforation Presenting as Dyspnea - Vincent Granier; Emmanuel Coche; Philippe Hantson; Maximilien Thoma (Case Reports in Medicine)
Introduction. Bochdalek hernia is a congenital defect of the diaphragm that is usually diagnosed in the neonatal period and incidentally in asymptomatic adults. Small bowel incarceration in a right-sided Bochdalek hernia is exceptional for an adult. Case Presentation. A 54-year-old woman was admitted for acute dyspnea, tachycardia, hypotension, and fever. Five days before, she had been experiencing an episode of diffuse abdominal pain. The admission chest X-ray was interpreted as right pleural effusion and pneumothorax with left mediastinal shift. Chest tube drainage was purulent. The thoracoabdominal CT examination suspected an intestinal incarceration through a right diaphragmatic defect. At laparotomy, a right-sided Bochdalek hernia was confirmed with a complete necrosis of the incarcerated caecum. Ileocaecal resection was performed, but the patient died from delayed septic complications. Conclusion. Intrathoracic perforation of the caecum is a rare occurrence; delayed diagnosis due to misleading initial symptoms may lead to severe complications and poor prognosis.